2009
DOI: 10.1088/0953-8984/21/13/134004
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic Fe on Cu(001) throughout the fcc-like phase: arguing from the viewpoint of the electronic structure

Abstract: The scientific enthusiasm for ultrathin Fe films on Cu(001) has now lasted for more than 20 years. Is there ferromagnetic iron with a face-centred cubic (fcc) structure? Does ferromagnetism in Fe hinge on the body-centred cubic (bcc) structure? In this contribution, we try to establish that the electron system gives evidence of ferromagnetic behaviour with fcc-like electronic bands. We examine a crystal-induced surface state, which is characteristic of fcc surface order. Furthermore, we compare electronic sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Among those substrates, Cu is characterized by the smallest lattice mismatch with bulk austenite and therefore has been thoroughly investigated (see, e.g. [8] and references therein). Other attempts are based on Ni, Au, Rh, and also on bcc or hcp substrates, such as W and Ru, respectively [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Among those substrates, Cu is characterized by the smallest lattice mismatch with bulk austenite and therefore has been thoroughly investigated (see, e.g. [8] and references therein). Other attempts are based on Ni, Au, Rh, and also on bcc or hcp substrates, such as W and Ru, respectively [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Past investigations with averaging techniques such as photoemission spectroscopy (PES) or magneto-optical Kerr effect (MOKE), for instance, detected a not-nil magnetic signal on thin Fe films and related it to the appearance of either low-or high-spin ferromagnetic γ (i.e., fcc) phases [18,19]. However, accurate structural studies performed by scanning tunneling microscopy revealed, also in those cases, the formation of bcc nuclei, calling for a more complex interpretation of the previous experimental results (see, for instance, the ongoing discussion on the growth of Fe on Cu(001) [20,21] or Cu(111) [3]). Our goal is, therefore, to improve, by means of electron spectroscopies, and also with spin resolution, the present understanding of the electronic and magnetic structure of thin Fe films, starting from a more accurate investigation of the spectroscopic signal which is expected from the fcc phase and from the bcc nuclei, and from an assessment of the overall sensitivity of averaging techniques such as PES to the onset of the phase transformation.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper [130] the results of numerous studies on the epitaxial growth of iron films on the surface of Cu(001) at room temperature have been summarized, and the following generalizations have been supposed. Up to four monolayers the Fe film is FM overall with the easy axis perpendicular to its plane (the 1st level).…”
mentioning
confidence: 99%
“…The issue of the possible presence of FM fcc Fe in the FeCu system has been raised repeatedly in the literature [8,109,[129][130][131][132]. It was tried to obtain by heat treatment of ball-milled (BM) both pure iron and iron in a mixture with copper.…”
mentioning
confidence: 99%